Mapping the Scientific Landscape of Psychological Crisis Affecting Child Sexual Abuse Victims: A Bibliometric Analysis - Rakhmawati, Ellya; Firtriana, Siti; Aditya, Dita Permata (Bulletin of Counseling and Psychotherapy, 2025)
This study explores the intellectual overview of psychological crisis in child sexual abuse (CSA) victims. Bibliometric analysis was performed to identify three primary terms “psychological crisis”, “child sexual abuse”, and “victims” between 2014 and 2024 which yielded 2,058 documents from WoS and Scopus databases after applying filtration criteria. The results were generated through VOSviewer and Biblioshiny. The study identified CSA as predominated keyword (11%), while psychological crises denoted with terms like trauma, anxiety, depression, and PTSD (1%). The psychological crisis marked as prevalence provides major impacts in recent research, while CSA remains an emerging topic that is evolving into specific areas such as punishment, emotions, victim blaming, and decision-making. The co-citation and authorship identified Finkelhor and Cohen J as fundamental researchers on CSA and child trauma, while Lyon TD as an influential author on CSA. The findings suggest that the research on CSA and its emotional effect on victims offers significant opportunities for further exploration in developing countries, particularly in Southeast Asia, alongside contributions from pioneer countries and established authors. The study concludes the need to advance research across several thematic areas in order to address existing knowledge gaps and advance scientific knowledge.